Nursing Activities of Clinic Nurses in Remote Parts of Japan’s Heavy Snowfall Areas - Hayashi, Tomoko; Hirasawa, Noriko (Al-Hijrah Indonesia, 2025)
Background: Heavy snowfall areas in Japan with inadequate medical care and transportation networks are referred to as remote areas. The remote-area clinics there contribute significantly to maintaining the good health of residents. However, there is a shortage of doctors and nurses. In Japan, where many deaths are expected, the role of nurses in remote-area clinics is expected to become more important than ever. Purpose: To clarify the nursing activities of nurses working in a remote-area clinic in Region A of N Prefecture and the challenges they face. Methods: Seven nurses working in a remote-area clinic underwent semi-constructive interviews and their responses were analyzed qualitatively and descriptively. Results: The following three categories of nursing activities in remote-area clinics were identified: “performing non-specialized tasks in parallel with nursing work,” “assessing the life and health of patients living in heavy snowfall areas,” and “exercising nursing expertise to help patients realize the life they desire. In addition, three categories of challenges perceived by nurses were extracted, such as